The role of diet in genotoxicity of fecal water derived from IBD patients and healthy controls. (October 2022) - Wang, Shan; Godschalk, Roger; Spooren, Corinne; de Graaf, Marlijne; Jonkers, Daisy; van Schooten, Frederik-Jan
Abstract: Certain dietary factors with anti-inflammatory and/or anti-cancer properties would be a promising preventive strategy for inflammatory bowel disease (IBD) patients against developing colitis-associated colorectal cancer (CAC). In this study, fecal water (FW) was obtained from 80 IBD patients and 20 healthy controls (HCs). The comet assay was applied to determine the DNA damage induced by FW, and the protective potential of FW against hydrogen peroxide (H2 O2 ) induced DNA damage in Caco-2 cells. Information on diet was obtained via food frequency questionnaires. The results showed that FW from IBD patients, especially patients with flares, induced higher levels of direct DNA damage in Caco-2 cells and showed less protection against H2 O2 -induced DNA damage, when compared to HCs. The DNA damage induced by FW was positively associated with consumption of processed meat and sugary foods, and nutrient intakes including heme iron and added sugars, whereas negatively correlated to intakes of soy products, and a dietary pattern characterized by high consumption of potatoes, white meat, nuts and seeds, eggs, legumes and soy products. FW from subjects with high coffee consumption protected against H2 O2 -induced DNA damage. These results can help to develop potential preventive strategies for IBD patients to reduce the CAC risk. Highlights: Measure the genotoxicity of FW by comet assay to estimate the risk for IBD patients of developing CAC. Fecal water from IBD patients increased the genotoxic potential of colonic epithelial cells. Specific dietary factors are associated with the genotoxicity of fecal water.